2015
DOI: 10.15252/embj.201591829
|View full text |Cite
|
Sign up to set email alerts
|

NSMCE 2 suppresses cancer and aging in mice independently of its SUMO ligase activity

Abstract: The SMC5/6 complex is the least understood of SMC complexes. In yeast, smc5/6 mutants phenocopy mutations in sgs1, the BLM ortholog that is deficient in Bloom's syndrome (BS). We here show that NSMCE2 (Mms21, in Saccharomyces cerevisiae), an essential SUMO ligase of the SMC5/6 complex, suppresses cancer and aging in mice. Surprisingly, a mutation that compromises NSMCE2-dependent SUMOylation does not have a detectable impact on murine lifespan. In contrast, NSMCE2 deletion in adult mice leads to pathologies re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
77
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(83 citation statements)
references
References 81 publications
5
77
1
Order By: Relevance
“…When the heterozygous Smc5 del oocytes were fertilized with sperm from the Smc5 flox/del, Hspa2-Cre males, the level of blastocysts obtained reduced by approximately half, which supports the fact that early stages of embryonic development are affected in embryos homozygous for mutation of Smc5. Homozygous mutation of other components of the SMC5/6 complex, Smc6 and Nsmce2, have also been shown to cause embryonic lethality (Jacome et al, 2015;Ju et al, 2013). Taken together with the IVF and MII data obtained for the 'juvenile' Smc5 cKO females (Figs 3 and 4, Table 2; Fig.…”
Section: Smc5 Is a Maternal-effect Genesupporting
confidence: 66%
See 1 more Smart Citation
“…When the heterozygous Smc5 del oocytes were fertilized with sperm from the Smc5 flox/del, Hspa2-Cre males, the level of blastocysts obtained reduced by approximately half, which supports the fact that early stages of embryonic development are affected in embryos homozygous for mutation of Smc5. Homozygous mutation of other components of the SMC5/6 complex, Smc6 and Nsmce2, have also been shown to cause embryonic lethality (Jacome et al, 2015;Ju et al, 2013). Taken together with the IVF and MII data obtained for the 'juvenile' Smc5 cKO females (Figs 3 and 4, Table 2; Fig.…”
Section: Smc5 Is a Maternal-effect Genesupporting
confidence: 66%
“…Therefore, it is possible that a heterozygous mutation of a SMC5/6 component could lead to age-related errors during oogenesis too. Supporting this notion, it has been shown that heterozygous mutation of Nscme2 results in increased incidences of micronuclei and polynucleation in MEFs (Jacome et al, 2015).…”
Section: Smc5/6 Protein Levels Are Diminished In Aging Oocytesmentioning
confidence: 85%
“…Recently, hypomorphic mutations of a Smc5/6 component, NSMCE2, have been reported to cause primordial dwarfism and microcephaly in human (Payne et al, 2014). Furthermore, SMC mutations are associated with cancer (Leiserson et al, 2015;Jacome et al, 2015). Cohesin mutations have been identified in myeloid leukemias (Leeke et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Second, NSMCE2 fails to form ionizing radiation (IR)-induced foci in mitotic cells neither it localizes to meiotic DSBs during meiosis. 2 Third, repair of meiotic DSB in yeast or IR-induced DSBs in mammalian cells are largely unaffected by SMC5/6 deficiencies. Finally, all members of the complex are essential in yeast, but HR is not.…”
mentioning
confidence: 99%
“…2 Moreover, NSMCE2 hypomorphism in humans also leads to a genomic instability syndrome that limits lifespan. 7 Hence, understanding the function of the SMC5/6 complex is still an important task, which beyond its academic interest might yield unanticipated insights with potential applications to human health.…”
mentioning
confidence: 99%